2016
DOI: 10.5465/amj.2014.0093
|View full text |Cite
|
Sign up to set email alerts
|

Status Matters: The Asymmetric Effects of Supervisor–Subordinate Disability Incongruence and Climate for Inclusion

Abstract: Growing workforce diversity increases the likelihood that supervisors and subordinates will differ along demographic lines, a situation that has important implications for their relationship quality and individual outcomes. In a sample of 1,253 employees from 54 work-units, we investigate the effects of differences in disability status between supervisors and subordinates on leader-member-exchange (LMX) quality and subsequent performance ratings, and find that incongruence in general is related to lower LMX qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 110 publications
6
96
0
Order By: Relevance
“…Internal experiences of PWD differ from reported observations of others, so a direct study of disabled employee perspectives is of importance in future research and practice (Santuzzi & Waltz, ). We thus responded to researchers' calls for more in‐depth inquiry into PWD in the workplace, to increase knowledge on how to benefit from disability diversity in the workforce (Colella & Bruyère, ; Dwertmann & Boehm, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Internal experiences of PWD differ from reported observations of others, so a direct study of disabled employee perspectives is of importance in future research and practice (Santuzzi & Waltz, ). We thus responded to researchers' calls for more in‐depth inquiry into PWD in the workplace, to increase knowledge on how to benefit from disability diversity in the workforce (Colella & Bruyère, ; Dwertmann & Boehm, ).…”
Section: Discussionmentioning
confidence: 99%
“…News reports indicated some firms in China would rather be fined by the government than recruit PWD (Qiao, ). Given the ubiquity of stigmatization and discrimination against PWD, there is a continuous call for the integration of PWD in the workplace, so organizations can benefit from a more diverse workforce (Colella & Bruyère, ; Dwertmann & Boehm, ). Since most of the current studies on disability were conducted in the United States, there is a limited understanding of integrating PWD into the workplace in other parts of the world (Colella, Hebl, & King, ).…”
mentioning
confidence: 99%
“…Omilion-Hodges and Baker (2017) defined LMX as the quality of the relationship between leaders and members. Dwertmann and Boehm (2016) performed a study with 1,253 participants and concluded that disability can contribute to the quality of the leader-member dyadic relationship. The differentiating factor of this theory as compared to others is that it specifically focused on the exchange in the leader-follower relationship (Northouse, 2016) whereas previous theories focused on one person in the relationship.…”
Section: Leader-member Exchange Theorymentioning
confidence: 99%
“…Richard (2000) shows that greater racial diversity has no direct relationship with performance, but, in firms that adopt growth strategies, the relationship is positive. Further, Avery (2011), Guillaume et al (2013), Garnero et al (2014) and Dwertmann and Boehm (2016) show that, in organizations with a more inclusive organizational climate, diversity is positively related to performance.…”
Section: Firms' Social Action As a Moderating Factormentioning
confidence: 99%
“…The frailty of relationships, at times marred by stigma and prejudice (Dwertmann & Boehm, 2016), and the lack of specialized institutions and of accessible physical structures are just a few of the issues at play in PwD insertion in the job market (Carvalho-Freitas & Marques, 2007 This study seeks to contribute to this discussion by investigating the relationship between the proportion of PwD and productivity in Brazilian firms. Since PwD are affected by negative perceptions of their contributions as a labor force (Stone & Collela, 1996, Dwertmann & Boehm, 2016, this study may offer information revealing possible and undesirable prejudice concerning PwD insertion in the job market. Thus, this study tests hypotheses that seek to evaluate the impact of the proportion of PwD on firm productivity in Brazil.…”
Section: Introductionmentioning
confidence: 99%